Overgrowth syndrome associated with a gain‐of‐function mutation of the natriuretic peptide receptor 2 (NPR2) gene. Issue 1 (20th November 2013) - Miura, Kohji; Kim, Ok‐Hwa; Lee, Hey Ran; Namba, Noriyuki; Michigami, Toshimi; Yoo, Won Joon; Choi, In Ho; Ozono, Keiichi; Cho, Tae‐Joon
ABSTRACT The signal pathway of the C‐type natriuretic (CNP) and its receptor, natriuretic peptide receptor 2 (NPR2) is involved in the longitudinal growth of long bones. Loss of function mutations at NPR2 cause acromesomelic dysplasia, type Maroteaux, while overproduction of CNP by chromosomal translocation and a gain‐of‐function mutation at NPR2 have been reported to be responsible for an overgrowth syndrome in three cases and one family, respectively. We identified a four‐generation family with an overgrowth syndrome characterized by tall stature, macrodactyly of the great toes, scoliosis, coxa valga and slipped capital femoral epiphysis, similar to those previously reported in association with CNP/NPR2 overactivity. The serum level of amino‐terminal proCNP was normal in the proband. A novel missense mutation of NPR2, c.1462G>C (p.Ala488Pro) was found to co‐segregate with the phenotype in this family. In vitro transfection assay of the mutant NPR2 revealed overactivity of the mutant receptor at baseline as well as with the ligand. This overgrowth syndrome caused by a gain‐of‐function mutation at NPR2 should be differentiated from Marfan or related syndromes, and may be categorized along with the overgrowth syndrome caused by overproduction of CNP due to its phenotypical similarity as overgrowth CNP/NPR2 signalopathy. © 2013 Wiley Periodicals, Inc.